De novo assembly of a genome-wide transcriptome map of Vicia faba (L.) for transfer cell research - Arun-Chinnappa, Kiruba S.; McCurdy, David W. (Frontiers in Plant Science, 2015)
Vicia faba (L.) is an important cool-season grain legume species used widely in agriculture but also in plant physiology research, particularly as an experimental model to study transfer cell (TC) development. Adaxial epidermal cells of isolated cotyledons can be induced to form functional TCs, thus providing a valuable experimental system to investigate genetic regulation of TC development. The genome of V. faba is exceedingly large (ca. 13 Gb), however, and limited genomic information is available for this species. To provide a resource for transcript profiling of epidermal TC development, we have undertaken de novo assembly of a cotyledon-enriched transcriptome map for V. faba. Illumina paired-end sequencing of total RNA pooled from different tissues and different stages, including isolated cotyledons induced to form TCs, generated 69.5M reads, of which 65.8M were used for assembly following trimming and quality control. Assembly using a De-Bruijn graph-based approach within CLC Genomics Workbench v6.1 generated 21,297 contigs, of which 80.6% were successfully annotated against GO terms. The assembly was validated against known V. faba cDNAs held in GenBank, including transcripts previously identified as being specifically expressed in epidermal cells across TC trans-differentiation. This cotyledon-enriched transcriptome map therefore provides a valuable tool for future transcript profiling of epidermal TC development, and also enriches the genetic resources available for this important legume crop species.